Learning ROS for robotics programming : a practical, instructive, and comprehensive guide to introduce yourself to ROS, the top-notch, leading robotics framework /: a practical, instructive, and comprehensive guide to introduce yourself to ROS, the top-notch, leading robotics framework. (2013) - Unknown
No abstract available